Rodzina Czechów na Wołyniu - Vaculik, Jaroslav (Karkonoska Państwowa Szkoła Wyższa, 2011)
The testimony of Volhyniai Czechs' family life are chronicles which were recorded by some Czech families from their arrival to Volhynia at the tum of the 60's and 70's of the 19th century to the 30's of the 20th century. The chronicles should serve as an advice for new generations of Czech minority. They show conditions in which the immigrants to Volhynia were beginning, their closeness, endogamy and complications connected with the establishment of Bolshevik and Nacist regime and also the postwar re-emigration.
Keywords: rodzina; Wołyń; Czesi